2008
DOI: 10.1128/aac.01424-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Herpes Simplex Virus Type 1 Infection by Cationic β-Peptides

Abstract: Previously, it was shown that cationic ␣-peptides derived from the human immunodeficiency virus TAT protein transduction domain blocked herpes simplex virus type 1 (HSV-1) entry. We now show that cationic oligomers of ␤-amino acids ("␤-peptides") inhibit HSV-1 infection. Among three cationic ␤-peptides tested, the most effective inhibition was observed for the one with a strong propensity to adopt a helical conformation in which cationic and hydrophobic residues are segregated from one another ("globally amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…11,12 These unnatural peptides can also act as scaffolds with sophisticated biological functions that include antibacterial magainin mimetics 13,14 as well as inhibitors of protein-protein interactions 15,16 and viral infections. 17,18 In a recent review, developments in structural characterization and in vitro and in vivo evaluation of foldamers document the extensive chemotherapeutic potential and diversity of cyclic and acyclic peptide backbones derived from natural and unnatural amino acids. 19 …”
Section: Introductionmentioning
confidence: 99%
“…11,12 These unnatural peptides can also act as scaffolds with sophisticated biological functions that include antibacterial magainin mimetics 13,14 as well as inhibitors of protein-protein interactions 15,16 and viral infections. 17,18 In a recent review, developments in structural characterization and in vitro and in vivo evaluation of foldamers document the extensive chemotherapeutic potential and diversity of cyclic and acyclic peptide backbones derived from natural and unnatural amino acids. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Viral attachment to cell surface was assessed at 4°C, which allows for HSV-1 binding but excludes entry (41), using cellular enzyme-linked immunosorbent assay (ELISA), as well as flow cytometry. The ELISA binding assay was performed as previously described with some modifications (2,31). Briefly, 96-well plates were seeded with A549 cells (2 ϫ 10 4 cells per well) and allowed to grow overnight.…”
mentioning
confidence: 99%
“…2). Tat and other highly cationic peptides have been shown to prevent cell attachment by HSV-1 (45). In cell enzyme-linked immunosorbent assay experiments, we found that Tat-only and Tat-Ebo have similar modest effects on viral attachment to cells (data not shown).…”
Section: Enhanced Activity Of Endosome-targeted Ebov C-peptides-mentioning
confidence: 54%